The contract of employment (Oxford, 2016)
"The contract of employment is the central legal institution of modern English employment law. It provides the foundation upon which most statutory employment rights are constructed; it provides a conduit for the implementation of norms negotiated in collective bargaining; and it continues to provide a contractual structure for the terms and conditions of employment for a significant proportion of the working population. The Contract of Employment provides the most ambitious and comprehensive treatise on the theoretical and doctrinal aspects of the English contract of employment in the common law world. Under the general editorship of Professor Mark Freedland, the text has been produced by a team of world leading experts in employment law. Part I examines the theoretical context to the contract of employment, studying its structure and development from a wide variety of theoretical and comparative perspectives. Part II provides an exposition and analysis of the doctrinal aspects of the contract of employment. The coverage of The Contract of Employment is unrivalled in its depth, detail and sophistication. The legal analysis is always informed by a keen sense of the modern labour market context of the contract of employment, and it is sensitive to contemporary challenges such as precariousness, the interaction with migration law, the role of legislation in the contract of employment, and the decline of collective bargaining. It will be the principal reference point for the practitioners, judges, and academics concerned with the contract of employment as a legal category, both nationally and internationally."